AFCRL scientific research in Greenland, 1967-1970 - Silverman, S. M.; Air Force Cambridge Research Laboratories (U.S.) (L.G. Hanscom Field, Bedford, Massachusetts : Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1971)
The AFCRL Geopole Observatory carries out a series of measurements of geophysical interest near the north pole of the geomagnetic dipole field. The nature of these measurements, the scientific and technical background, and the status during the period 1967-1970 are described. A section presenting the data availability is also included. Research supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, L.G. Hanscom Field, Bedford, Massachusetts. Aeronomy Laboratory, Project 7661. AD0736759 (from http://www.dtic.mil). "17 September 1971." Includes bibliographical references. The AFCRL Geopole Observatory carries out a series of measurements of geophysical interest near the north pole of the geomagnetic dipole field. The nature of these measurements, the scientific and technical background, and the status during the period 1967-1970 are described. A section presenting the data availability is also included. Mode of access: Internet.